Opinião de Estudantes Universitários sobre a educação a distância (EaD), no contexto das ciências farmacêuticas - Hildonice de Souza Batista; Aníbal de Freitas Santos Júnior (Universidade Estadual de Campinas, 2012)
This article aims to discuss the inclusion of distance education in the practice of Pharmaceutical Sciences. The study population consisted of 200 individuals (students) in the city of Salvador / Bahia. For data analysis, were used in semi-structured questionnaires, in which students interviewed expressed their opinions about distance education, in the course of Pharmacy. Students highlighted the use of the Internet as a tool to aid in research and scholarship, as well as other alternative.